2001
DOI: 10.1007/s004040000122
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome at age 40 and older

Abstract: Nulliparous women age 40 or over have a higher risk of operative delivery than do younger nulliparous women. This increase occurs in spite of lower birth weight and gestational age and may be explained by the increase incidence of obstetric complications. Although maternal morbidity was increased in the older women, the overall neonatal outcome did not appear to be affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
60
4
22

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 0 publications
20
60
4
22
Order By: Relevance
“…These findings were in accordance with similar findings showed in study done by Jolly M [15] in which incidence of abruptio placenta, preterm labour in the study group were (0.63%, 1.58%) respectively while in the control group were (0.45%, 1.03%) respectively, similar finding showed byZiadeh S [13] study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings were in accordance with similar findings showed in study done by Jolly M [15] in which incidence of abruptio placenta, preterm labour in the study group were (0.63%, 1.58%) respectively while in the control group were (0.45%, 1.03%) respectively, similar finding showed byZiadeh S [13] study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study the mean birth weight in study group (3.06 + 0.67) Kg which was significantly lower than control group (3.39+ 0.33) Kg these findings in accordance to the study done by Ziadeh S [13] who showed mean birth weight in his study group (3.21 + 0.5) Kg which was significantly lower than control group (3.32+ 0.1) Kg, Jahromi BN [15] also found similar result in his study. In present study, mean APGAR score at 5 th minute in this study group was (8.42 + 1.14) and in control group was (8.46 + 0.62) the difference was statistically not significant (P > 0.05), this is in contrast to studies done by JahromiBN [15] and Berkowitz [4] who showed the incidence of APGAR score at 5 th minute significantly lower in the older women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The association between advanced maternal age and increased risk of chromosomal abnormalities and spontaneous abortion has been well documented in studies 2,22 .…”
Section: Introductionmentioning
confidence: 94%